Benign oesophageal stricture in Barrett's columnar epithelialised oesophagus and its responsiveness to conservative management. Issue 12 (December 1988) - Atkinson, M; Robertson, C S
Abstract : The response to treatment of peptic oesophageal stricture associated with columnar lined (Barretts) oesophagus (CLO) has been compared with that in peptic stricture without CLO. Benign oesophageal stricture was present in 23 (41%) of 56 patients consecutive with CLO. In 18 the stricture lay at the squamocolumnar mucosal junction and was associated with reflux oesophagitis, in five it was situated in the columnar lined segment and in four of these it was known to have been preceded by a chronic ulcer at the site of the stricture. Controls were an age and sex matched group of patients with benign stricture related to reflux oesophagitis unassociated with columnar epithelialisation. CLO associated strictures involving squamous mucosa were situated significantly (p less than 0.01) higher in the oesophagus than non-CLO strictures. The response to endoscopic dilatation and active medical treatment was significantly better, as judged by the need for subsequent dilatation (p less than 0.01) in the CLO than in the non-CLO group. It is concluded that associated columnar epithelialisation of the oesophagus is not in itself an indication for antireflux surgery in the management of benign stricture and these usually respond well to dilatation and medical treatment.